Clock Synchronization Algorithm for Structural Modal Measurement. (22nd April 2022) - Hu, Junliang; Li, Kai; Yan, Chaoxian; Guo, Huawei; Cui, Nannan; Huang, Shiping; Ding, Xiaoyan
Abstract : The modal of a structure is the natural vibration characteristic of the structure, which is very important for damage identification of the system. To accurately measure the structural modal, it is necessary to perform clock synchronization operations on the vibration sensors at each measuring point of the structure. This paper uses an improved TSPN algorithm for clock synchronization. It is assumed that the delay of the data in the transmission process obeys normal distribution. The fitting degree of a normal distribution is tested by fitting the delay distribution curve. Then, an interval estimation method is used to estimate the delay. The synchronization of multiple sensors and onsite structural modal testing verifies the correctness of the process after synchronization. The method in this paper is suitable for MCU-based vibration sensors to perform clock synchronization for structural modal measurements.